Entrepreneurial marketing in tourism enterprises: findings from three enterprises in Finland - Suomi, Kati; Lemmetyinen, Arja; Franzén, Riikka (Edward Elgar Publishing, 2025)
This chapter focuses on entrepreneurial marketing in tourism enterprises. It discusses the literature on entrepreneurial marketing in general and in tourism enterprises in particular. The chapter provides contemporary examples of entrepreneurial marketing for tourism enterprises by introducing three case examples from different tourism sectors in Finland - agritourism, boutique hotels, and music festivals. The results show that all the case enterprises utilize their embeddedness in the local community as their strength, whether building on the history, culture, use of language, or networks. The chapter classifies characteristics of entrepreneurial marketing in tourism enterprises into four upper-level categories: brand identity building, marketing communications, proactivity, and resource leveraging. The study introduces an overview of entrepreneurial marketing in tourism, suggesting that brand identity building and marketing communications represent an enterprise’s marketing approach, whereas proactivity and resource leveraging represent an entrepreneurial approach. The chapter underlines the importance of managing seasonality in entrepreneurial marketing of tourism enterprises.
Handbook of Tourism Entrepreneurship